One piece. Collection no. 13 [videorecording (DVD)]. (Funimation, 2015)
The assault on Enies Lobby rages on as Spandam drags Robin towards the towering Gates of Justice! Zoro's demonic nine-sword fighting style sets the stage for a blistering barrage of heroic attacks as the Straw Hats inch ever closer to a joyous reunion with their captured crewmate. Thankfully, Luffy and his mates manage to emerge victorious, but after bidding a fiery farewell to the Going Merry, these pirates won't be going anywhere.